A retrospective study of psychotropic drug treatments in bipolar disorder at acute and maintenance episodes - Jing, Pan; Su, Jianjun; Zheng, Chengying; Mei, Xi; Zhang, Xiaobin (Frontiers in Psychiatry, 2023)
Background: Bipolar disorder (BD) is predominantly treated with psychotropic drugs, but BD is a complex medical condition and the contribution of psychotropic drugs is not clear. The objectives of this study are: 1) to present psychotropic drugs used in patients with BD; 2) to access changes of psychotropic drug treatments in acute and maintenance episodes. Methods: The study retrospectively evaluated the medical records of inpatients in the Ningbo Kangning hospital from January 2019 to December 2019. The medical history of each subject was collected completely, including sociodemographic (gender, age, marital status, and so on) and clinical characteristics at baseline and within 12 months of admission. Results: The study ultimately included 204 patients with BD. After12 months, 73.0% of the patients still took drugs. Mood stabilizers (72-90%) and antipsychotics (77-95%) were still the most important drugs in patients with BD. Antidepressants (34-40%) and benzodiazepines (20-34%) were the other frequently used drug classes. For mood stabilizers, 40-56% of patients were prescribed Lithium. For antipsychotic, 54-65% of patients were prescribed quetiapine. Sertraline (6-9%) and Fluoxetine (5-9%) were the antidepressant that most frequently prescribed. Lorazepam (10-18%) was the most commonly used benzodiazepine. In psychotropic polypharmacy, the most frequently taken was Mood stabilizer (MS) plus antipsychotic (AP) co-treatment, about 36-44% of all patients. 35-48% of patients treated by 2 psychotropic drugs and 24-36% received 3. Conclusions: The first 6 months after treatment is very important to medication adherence. Mood stabilizers and antipsychotic remained the primary treatment for BD. Antipsychotic is on the rise in the treatment of BD.